Rekonstruksi pelayanan prima dalam Biro Haji dan Umrah: Studi Research Library terhadap Strategi Pelayanan Jamaah pada BIM Tour and Travel - Muammar Kadhafi; Jauharotina Alfadhilah (PT. Hasba Edukasi Mandiri, 2026)
The increasingly competitive development of Hajj and Umrah travel agencies in Indonesia has encouraged every religious travel agency to improve service quality to build pilgrim trust and satisfaction. This study aims to analyze the reconstruction of excellent service at BIM Tour and Travel through pilgrim service strategies. The study uses a qualitative approach with library research methods through the review of literature, journals, and documents related to Hajj and Umrah services. The research analysis uses the SERVQUAL theory which includes tangibles, reliability, responsiveness, assurance, and empathy. The results show that the reconstruction of excellent service can be achieved through increasing service transparency, strengthening human resource quality, humanistic communication, as well as spiritual services and worship assistance according to the needs of pilgrims. BIM Tour and Travel's service strategy is realized through manasik guidance, worship assistance, consultation services, and personal services oriented towards pilgrim satisfaction. This strategy has an impact on increasing trust, satisfaction, and the competitiveness of Hajj and Umrah travel agencies.